Financing systems in rural agricultural chains: an unsuccessful case in producing cucumbers in Zarcero, Costa Rica - Valenciano Salazar, Jorge Andrey (2013)
Using a case study of the Association of Crop Producers under Controlled Environment (Asociación de Productores de Cultivos Bajo Medio Controlado - APROMECO), based in Zarcero, Costa Rica, this article shows that credit is an essential element for small and medium-sized agricultural producers to gain access to cutting-edge technology that would enable them to connect with foreign agents and thus be part of an international chain. However, credit policies are not sufficient to ensure the success of these producers, as connecting to a global chain is just the beginning of a long process for local producers, who must find, together with public sector institutions, the necessary strategies to stay within the chain.